The drought crisis in the Central Highlands of Vietnam - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
As an impact of the ongoing El Niño Southern Oscillation (ENSO) phenomenon, serious drought has been occurring in the Central Highlands of Vietnam and has caused varying degrees of damage to agriculture and the livelihoods of people in the region. On 15 March 2016, the Vietnamese government and the United Nations Development Programme (UNDP) organized a meeting with donors, international organizations and other partners to discuss joint efforts for drought response and recovery. Another meeting was presided by the Ministry of Agriculture and Rural Development (MARD) Minister and the UN Resident Coordinator on 30 March 2016 to report on the recent rapid assessment of current natural hazards and call for short-, medium and long-term support from the international community. MARD recognizes that this crisis and its subsequent effects (e.g. inundation after the drought) will recur in the future and that there is a need to prepare and plan for necessary response measures. In response to this urgent call, the CGIAR Centers operating in Vietnam, in collaboration with MARD, organized a joint field assessment in the Central Highlands to have a first-hand observation and assessment of the drought problem currently being experienced by the region. The CGIAR interventions recommended based on the assessment may support the short-, medium- and long-term planning in response to the impacts of climate change. The collective strength that the CGIAR could contribute is in downscaling some of the global data and analyses to Vietnam scenarios and forecasts for their planning, recommending climate-smart agriculture (CSA) options for integration in current and future donor/development interventions, and identifying opportunities in research for development (R4D) for future preparedness.